Short-pulsed Q-switched Thulium doped fiber laser with graphene oxide as a saturable absorber - Kasim, Nabilah (Elsevier, 2018)
This paper reports a generation of short-pulsed thulium-doped fiber laser (TDFL) in Q-switching operation incorporation of homemade graphene oxide (GO) saturable absorber (SA). The GO SA is embedded with a polymer to form a GO film. A piece of the GO film is integrated into the TDFL cavity for generating a self-started Q-switching operation at 1943 nm wavelength. The 3-dB bandwidth, repetition rate, and pulse width of the laser are obtained as 9 nm, 15.76 kHz–25.08 kHz, and 5.08 μs–4.2 μs, respectively. The maximum pulse energy of 0.698 μJ obtainable at 344 mW pump power, with a peak power of 137.4 mW. With a shortest pulse width size at a maximum pump power of 491 mW, the higher peak power is determined about 162 mW. By integrating our stable Q-switched laser with an optical amplifier, numerous applications such as a material cutting with the eye-safe feature can be realized. This shows a small piece of the GO can modulate a light and use for the pulsed laser industry.